The NSB control: a behavior-based approach for multi-robot systems - Antonelli Gianluca; Arrichiello Filippo; Chiaverini Stefano (Paladyn, 2010)
The paper presents an overview on the use of a behavior-based approach, namely the Null-Space-based Behavioral (NSB) approach, to control multi-robot systems in a wide application domain. The NSB approach has been recently developed to control the motion of generic robotic systems; it uses a projection mechanism to combine the multiple, prioritized, behaviors that compose the robotic mission so that the lower priority behaviors do not effect the higher priority ones. In this paper we describe how the NSB approach has been used to control different multi-robot systems (e.g., composed of wheeled and marine robots) to achieve missions such as formation control, entrapping/escorting of targets, control of mobile ad-hoc networks, flocking, border patrol and cooperative caging.